The Paradox of the Sovereignty of the Constitutional Court in the Context of Protecting Democracy and the Constitution in Indonesia - Mutiasi, Novia; Kristanto, Budi (Al-'Adl, 2025)
This research aims to examine the position and authority of constitutional institutions in maintaining democratic stability and constitutional supremacy in Indonesia, especially in the context of the potential paradox of sovereignty that can arise from the role of law testing. In particular, the study highlights how the judiciary functions as a guardian of constitutional values, but at the same time risks exceeding the limits of authority that could disrupt the principle of checks and balances and government stability. This study uses normative legal methods with a doctrinal approach combined with bibliometric analysis through the VOSViewer application to map the trends of literature and related legal references. The results of the study show that the institution plays a crucial role in correcting policies that are not in line with the 1945 Constitution. However, its final and binding authority has the potential to create tensions with the executive and legislative institutions and create far-reaching legal uncertainty. Therefore, it is necessary to strengthen supervisory mechanisms, increase transparency, and develop cross-institutional constitutional dialogue to ensure the balance of power in a democratic constitutional system.